2022
DOI: 10.2147/ijgm.s353244
|View full text |Cite
|
Sign up to set email alerts
|

Role of MicroRNA-223 and MicroRNA-182 as Novel Biomarkers in Early Detection of Colorectal Cancer

Abstract: Background Colorectal cancer is a common and lethal disease. It is estimated that approximately 145,600 new cases of large bowel cancer are diagnosed annually in the USA. MiRNA-223 and miRNA-182 have been reported in various cancers, such as lung, gastric, breast and colorectal cancer and proposed to be valid and reliable for diagnosis as well as prognosis. Aim This study aimed to determine the role of miR-223 and miR-182 as novel biomarkers for early detection and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(27 reference statements)
2
1
0
Order By: Relevance
“…Increasing evidence has shown that abnormally expressed miRNAs might be considered as the prognostic markers. [33,34] Our findings confirmed the obvious downregulation of Previous reports revealed that breast cancer could promote RANKL-induced osteoclastogenesis in vitro, [35] we then explored whether miR-506 affected the RANKL-induced osteoclastogenesis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Increasing evidence has shown that abnormally expressed miRNAs might be considered as the prognostic markers. [33,34] Our findings confirmed the obvious downregulation of Previous reports revealed that breast cancer could promote RANKL-induced osteoclastogenesis in vitro, [35] we then explored whether miR-506 affected the RANKL-induced osteoclastogenesis.…”
Section: Discussionsupporting
confidence: 86%
“…Increasing evidence has shown that abnormally expressed miRNAs might be considered as the prognostic markers. [ 33,34 ] Our findings confirmed the obvious downregulation of miR‐506 in breast cancer in tissue samples of breast cancer patients and cell lines, indicating that miR‐506 might be a potential prognostic marker for breast cancer.…”
Section: Discussionsupporting
confidence: 74%
“…These results suggest that miR-223 could be a potential therapeutic target in patients with CRC [166]. In addition to these data, the quantification of miR-223 levels in plasma could be an accurate and reliable biomarker for the early identification and prognosis of CRC [168,169].…”
Section: Mirnas and Msi-h Status Mir-26bmentioning
confidence: 71%
“…In the transcriptionally active phase, miR-223 has the potential to modulate NLRP3 mRNA [ 64 ], and miR-223 can attach to a highly conserved region of the 3′UTR of NLRP3 mRNA and consequently inhibit protein translation, according to an in silico analysis [ 65 ]. While miR-223 has been associated with decreased NLRP3 expression and IL1β secretion in inflammatory circumstances, there is inconclusive evidence regarding its effects in sporadic CRC [ 66 , 67 , 68 ]. A recent study revealed that wild-type miR-223 may exert a more potent anticancer effect in sporadic CRC when compared with glibenclamid [ 69 ].…”
Section: Epigenetic Regulation Of Inflammasomes In Crcmentioning
confidence: 99%